Assessment of the Quality of Neonatal Health Care at the Peadiatric Unit of the University of Ghana Hospital - Boateng, A.A. (University of Ghana, 2016)
Background: Quality of care for neonates is one of the key factors that contributes to the survival of babies in the under-five group. So the assessment of the quality of care given at the first 28 days of the baby’s life is very crucial and upon which improvement of health service delivery can be undertaken. The Donabedian model of quality of care was adopted in the assessment of quality of care (structure, processand output). The aim of the study is to explore on the perceptions about mothers of new-borns, availability of adequate and skilled human resources for neonatal care and equipment and care processes at the paediatric unit of the University of Ghana Hospital Legon. Method: The study was a cross-sectional survey employing both qualitative and quantitative approaches. Exit interviews were carried out for 36 mothers whose neonate were admitted with neonatal morbidities, in-depth interview was done with 14 staff of the paediatric ward to analyse the availability of human workforce available for neonatal care delivery. Direct observation was done using the Ghana Health Service observation guide to assess the availability of equipment and care processes available. Descriptive analysis was done using Stata version 12 and interviews done were coded into themes for analyses. Result: Mother’s perception about care was portrayed by a high satisfaction index being 61.10% and their rate on neonatal care is 58.35%. Staff with skills in neonatal care were inadequate. Some basic equipment’s for neonatal care were not available and some available equipment were inadequate for neonatal care at the paediatric unit of the University of Ghana Hospital Legon. Conclusion: Mothers were dissatisfied with babies being put together with other babies in the same ward and staff also complained of the same situation, lack of adequate staff and basic equipment. It is recommended that the management get an intensive care unit with adequate staff and equipment.
Thesis(MPH)-University of Ghana, 2016
Keywords: Neonatal Health Care; Peadiatric Unit